1972
DOI: 10.1017/s0022172400022075
|View full text |Cite
|
Sign up to set email alerts
|

The development of TRIC organisms in cell cultures during multiple infection

Abstract: SUMMARYThe relationship between multiplicity of infection and the yield of organisms and of polysaccharide was studied in BHK 21 cells infected with TRIC organisms. Although an increase in the multiplicity of infection resulted in an increase in the absolute number of organisms per culture, there was a decrease in relation to the number of infecting organisms. The amount of polysaccharide produced was independent of multiplicity of infection; it was not limited by the concentration of glucose in the medium. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…the yield from one hundred 250 ml Falcon Plastics flasks). The yield and ratio of infective to total elementary bodies were similar to those from infected monolayer cells (Evans, 1972). Provided that most of the infected cells remained whole the yield of elementary bodies/ ml of culture was greatest about 60 h after infection.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…the yield from one hundred 250 ml Falcon Plastics flasks). The yield and ratio of infective to total elementary bodies were similar to those from infected monolayer cells (Evans, 1972). Provided that most of the infected cells remained whole the yield of elementary bodies/ ml of culture was greatest about 60 h after infection.…”
Section: Discussionsupporting
confidence: 58%
“…As in TRIC infections of monolayer cultures (Reeve & Taverne, 1967;Evans, 1972), polysaccharide production in suspended cells accompanied the development of elementary bodies. Although the maximum polysaccharide concentration/culture was reached 50 to 60 h after infection of suspended cells, the average polysaccharide content of inclusions continued to increase for at least 30 h after this (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that chlamydiae produce an enzyme (or enzymes) that directs polysaccharide synthesis, although the host cell controls the amount of polymer formed in the inclusion (Jenkin & Fan, 1971 ;Evans, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide associated with TRIC-infected BHK cells is degraded enzymically by cell homogenates at neutral or slightly acid pH (Evans, 1972;Garrett & Harrison, 1973). To avoid this, cells infected 48 h earlier were therefore harvested by centrifugation at 600 g for 10 min and extracted with 5 % (w/v) trichloroacetic acid (TCA) for I h at o "C; preliminary experiments showed that TCA extracted all the polysaccharide from infected cells.…”
Section: )mentioning
confidence: 99%